Implementation of the Wana Kertih Concept in Building Community Legal Awareness toward the Preservation of Customary Forests in Bayung Gede Customary Village, Kintamani District, Bangli Regency - Ida Bagus Sudarma Putra; I Made Sugita; I Made Sudharma; Dewa Putu Tagel (NOTARIIL Jurnal Kenotariatan, 2026)
The implementation of the Wana Kertih concept in building community legal awareness toward the preservation of customary forests in Bayung Gede Customary Village demonstrates that the Wana Kertih concept is a sekala niskala (material-spiritual) concept that integrates spiritual, ecological, and social dimensions based on the tued kayu myth and Bali Mula cosmological beliefs. This concept is manifested through the ritual of hanging placenta at the Bukak Tree in the placenta cemetery (setra ari-ari), reflecting the Catur Sanak philosophy and Tri Hita Karana values. Effective implementation occurs through three elements: (1) Legal substance in the form of unwritten awig-awig (customary law) with the imposition of arta danda penalties of 200 ancient kepeng coins based on restorative customary sanctions; (2) Legal structure through the Ulu Apad Paduluan Saih Enembelas system led by Jero Kubayan Mucuk with communal supervision mechanisms; (3) Community legal culture reflecting high legal awareness, despite the majority of the population being dominated by elementary and secondary education graduates (approximately 59.34% or nearly 70% including those who have not completed elementary school), demonstrating that Wana Kertih has become living law with stronger binding force compared to formal law because it originates from spiritual awareness internalized through daily social-spiritual practices and cosmological beliefs embedded over hundreds of years. This concept proves the effectiveness of community-based local wisdom in sustainable customary forest preservation without reliance on formal state law enforcement.